(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study explores the pedagogical foundations of individual educational trajectories (IETs), emphasizing constructivist learning, curriculum differentiation, and self-regulated learning. IETs enhance student motivation, autonomy, and academic success by tailoring education to individual needs. The paper highlights assessment strategies, technology integration, and collaborative approaches to implementing effective personalized learning models.